CASE OF DESCEMET MEMBRANE DETACHMENT POST-CATARACT SURGERY - Khalid, Maham; Malik, Hajra Arshad; Asrar, Aamir; Khan, Hina; Asrar, Maha (Journal of Ayub Medical College Abbottabad, 2020)
Descemet Membrane Detachment is a vision-threatening complication of Cataract Surgery. If not treated promptly it can lead to serious vision impairment with the possible need for corneal transplantation. We present a case report of a 60 years old female who presented with blurry vision post phacoemulsification and lens placement after a cataract in the left eye. She was diagnosed with Descemet membrane detachment on slit-lamp examination that was confirmed on Anterior-segment Optical Coherence Tomography and treated with intracameral 20% SF6 injection. There was a marked improvement in her vision with complete resolution of corneal oedema. Conclusion: Anterior Segment OCT can be used as a diagnostic tool to accurately ascertain the site and extent of detachment and monitor disease progress. 20% Sulfur-hexafluoride intracameral injection can be used as a surgical option for large, central detachments. Keywords: Descemet Membrane, Cataract, Tomography Optical Coherence, Corneal Opacity